Antijudaism och antisemitism i den tyska kyrkokampen. Ett bidrag till ansvarsproblemet i den teologiska judaistiken - Heinonen, Reijo (Nordisk judaistik, 1985)
The purpose of this article is to shed light on the impact of the church, meaning its teachings and theological research, on the actions considering "the Jewish question" in Germany in the 1930s. Antijudaism and antisemitism in the tradition of theological interpretation was one reason why the Church did not interfere when Hitler was on his way to power, neither when the anti-Semitic actions took more and more radical forms of expression. A process of "Germanization" of the church made for example the Bible a political instrument, and many church members and theologians wanted to prove that Christianity had no connection to Judaism.